2016
DOI: 10.1002/eji.201546178
|View full text |Cite
|
Sign up to set email alerts
|

Aging of the immune system: Focus on inflammation and vaccination

Abstract: Major advances in preventing, delaying or curing individual pathologies are responsible for an increasingly long life span in the developed parts of our planet, and indeed reaching 8–9 decades of life is nowadays extremely frequent. However, medical and sanitary advances have not prevented or delayed the underlying cause of the disparate pathologies occurring in the elderly: aging itself. The identification of the basis of the aging processes that drives the multiple pathologies and loss of function typical of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
302
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 378 publications
(320 citation statements)
references
References 182 publications
8
302
0
10
Order By: Relevance
“…In addition, it is likely that structural features including small airway calibre may make infants more prone to critical airway narrowing and resultant hypoxia in the face of lung inflammation 28 . The elderly have a senescing immune system and are therefore less able to induce appropriate responses to invading pathogens 30, 31 . It is possible that the innate immune response in these two at-risk groups is suboptimal, which results in an unbalanced immune response and inefficient balance between viral control and immunopathology.…”
Section: Rsv Infectionmentioning
confidence: 99%
“…In addition, it is likely that structural features including small airway calibre may make infants more prone to critical airway narrowing and resultant hypoxia in the face of lung inflammation 28 . The elderly have a senescing immune system and are therefore less able to induce appropriate responses to invading pathogens 30, 31 . It is possible that the innate immune response in these two at-risk groups is suboptimal, which results in an unbalanced immune response and inefficient balance between viral control and immunopathology.…”
Section: Rsv Infectionmentioning
confidence: 99%
“…2 IL-6 is a multifunctional cytokine that orchestrates innate and adaptive immunity, induces the acute phase response, and is involved in bone metabolism by acting on osteoclasts and promoting osteoclastogenesis, as well as in the control of vascular permeability by inducing the production of vascular endothelial growth factor. 2 It represents a critical cytokine in infection, cancer and inflammation, and it has been demonstrated that increased IL-6 levels are associated with disease settings such as several chronic inflammatory pathologies and cancer, in contrast to the relative low (1)(2)(3)(4)(5) pg/mL) physiological concentrations found in human serum. 1 Moreover, increased levels of circulating IL-6 are commonly used as indicator of inflammaging.…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, increased levels of circulating IL-6 are commonly used as indicator of inflammaging. 3 Besides serving as a biomarker for inflammation processes, IL-6 is now being targeted by therapeutic strategies to inhibit its pathway.…”
Section: Introductionmentioning
confidence: 99%
“…L'invecchiamento immunitario negli anziani è definito primariamente da cambiamenti delle sottopopolazioni delle cellule T e dall'alterazione della loro funzione. Questo include un aumento di linfociti TCD8+ circolanti con un'espansione delle cellule TCD4+ e CD8+ memoria, fenomeno descritto come "memory inflation", con predominanza di cloni specifici per Citomegalovirus che aumentano con l'età (12,13). Attualmente non è ancora chiaro se la carenza di sviluppo, omeostatica o funzionale delle cellule T regolatorie CD4+ contribuisca allo sviluppo del profilo di invecchiamento immunologico (9).…”
Section: Aspetti Immunologiciunclassified